Effect Of The Application Of Different Cooking Periods On The Physicochemical Properties And Microbial Safety Of Hot Pepper Sauce - Ebenezer Narteh Nartey; Emmanuel Tei-Mensah; Stephen Adusei; Doreen Asante; Charity Abaati (IPTEK The Journal for Technology and Science, 2021)
Hot pepper sauce is a frequently used product in most Ghanaian homes, schools, and restaurants, which occasionally serves as condiments. The cooking period during the production process of hot pepper sauce results in physicochemical changes, which affect the quality and safety of the sauce. The study seeks to determine the effect of the application of different cooking times on the physicochemical properties and microbial safety of hot pepper sauce. The cooking periods were 10 minutes, 20 minutes, 30 minutes, and 1 hour for samples A, B, C, and D. Standard physicochemical and microbiological techniques were employed in the various analysis. Sample D (1 hour cooked) recorded the least moisture and ash content, insoluble acid ash, and a statistically significant acid value (P